HOW DOES THE WRITER SAVE THE READER'S FACE? (Descriptive Study at Using Face Concept in Politeness Strategy in some Notices in Singapore) - Siti Suharsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
Giving command to other people should consider many things: choice of word, context of situation and social context. Those can help us, both as speaker or writer, avoid the rudeness and threaten other's face. This paper is intended to take term